Production of Porous Silica from Rice Husk Using Cetyltrimethylammonium Bromide to Remove Dyes in Aqueous Solution - Nguyen, Van Doan; Nguyen, Thi Mai; Dao, Thi Cam Vi; Nguyen, Thu Huong; Vu, Tuan Cuong; Le, Trung Phong; Nguyen, Thu Huyen; Vu, Anh Tuan (JST: Engineering And Technology For Sustainable Development, 2024)
Porous silica was prepared from rice husk (RH) for the removal of organic dye (Janus Green B, JGB). The as-prepared samples were analyzed by using emission scanning electron microscope (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and N2 adsorption/desorption isotherm. The as-prepared silica was an amorphous and mesoporous material and the textural properties depended on the assistance of cetyltrimethylammonium bromide (CTAB). The SiO2-15 sample had a large surface area of 544.5 m2/g, a high pore volume of 1.259 cm3/g and average pore size of 9.4 nm. The performance of the SiO2-15 was evaluated by the removal of JGB and the effects of reaction parameters on the adsorption process were extensively explored. The optimum conditions for the removal of JGB were adsorbent dosage of 0.5 g/L, solution pH of 6, JGB concentration of 30 ppm, and temperature of 30 oC. The removal efficiency of JGB on SiO2-15 was 98.83% in 60 min with a rate constant of 0.025 g.mg-1.min-1. In addition, the adsorption is fast in the initial 5 min and the adsorption isotherms were investigated.